Pembekalan Pasien Tuberkulosis Tentang Bahaya Resistensi Multipel Obat Antituberkulosis di Kota Medan - Humairah Medina Liza Lubis; Emni Purwoningsih; Ratih Yulistika Utami (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2020)
Tuberculosis (TB) is an infectious disease caused by bacterial infection Mycobacterium tuberculosis (MTB). TB infection is still a health problem in the world and Indonesia since 1989-1992 there has been an increase in this disease, which is associated with an increase in the HIV / AIDS epidemic, urbanization and migration due to the recession that hit the world. Along with the increase in this disease a new problem arises, namely TB with multiple anti-tuberculosis drug resistance (Multidrug Resistant Tuberculosis / MDR-TB). The community service objectives are (1) finding new TB patients, MDR-TB and drug cessation cases, (2) providing health debriefing about the dangers of Multiple Anti-Tuberculosis Drug Resistance to partners, (3) providing counseling about healthy food and balanced nutrition to partners , (4) empower TB health cadres and Drug Drugs Supervisors in each neighborhood in Pahlawan Village as a system of coordination in handling TB in their respective work areas. There were 30 new cases of TB and 5 cases with MDR TB that needed serious treatment from the medical staff and related health services.